Exercise-Induced Bronchospasm Diagnosis in Sportsmen and Sedentary. - Messan, Folly; MARQUESTE, Tanguy; AKPLOGAN, BARNABÉ; DECHERCHI, Patrick; GRELOT, Laurent (My University, 2012)
This paper aims to identify factors that may account for the high values and varied prevalence of exercise-induced bronchospasm (EIB), which occur in the population of athletes. Journal articles, indexed and peer reviewed, published in the MEDLINE and SPORTDiscus database were screened using a computer search. Keywords as “prevalence,” “exercise,” “bronchospasm,” and “athletes” were crossed. The diagnosis of EIB based on the questionnaire or maximal decrease of ventilatory parameters was considered as inclusion criteria and selection of articles. Analysis of selected articles reveals higher values and varied prevalence of EIB (11–55%) compared to those in the general population (4–20%). Evaluation criteria of EIB are those based on the characteristics of sedentary subjects. Criteria sometimes do not seem adapted to speciﬁc sports. This paper suggests a diﬀerential diagnostic approach which takes account of both the EIB characteristics of sedentary and those of sportsmen.
Keywords: Bronchospasm; Exercise; sportmen; sedentary.